An Historical Sketch of Chinese Historiography - Wu, Huaiqi (China Academic Library,, 2018)
This book systematically traces the development of Chinese historiography from the 2nd century B.C. to the 19th century A.D. Refusing to fit the Chinese historical narration into the modern Western discourse, the author highlights the significant questions that concern traditional historians, their philosophical foundations, their development over three thousand years and their influence on the intelligentsia. China is a country defined in terms of its history and its historians have worked hard to record the past. However, this book approaches Chinese history from the very beginning not only as a way of recording, but also as a way of dealing with the past in order to orient the people of the present in the temporal dimension of their lives. This book was listed as the key textbook of the "Eleventh Five-year Plan" for college students in China.